Credit risk and the role of capital adequacy regulation - Thilo Pausch; Peter Welzel (Universität Augsburg, Institut für Volkswirtschaftslehre, 2002)
Using the industrial organization approach to the microeconomics of banking we model a large (Monti-Klein) bank which is risk neutral and faces credit uncertainty in its loan business. The impact of capital adequacy regulation and the effect of changes in risk on deposit and loan rates are analyzed. We then show that capital adequacy regulation induces the bank to behave as if it were risk averse. Finally, we examine risk management with credit derivatives in the framework of the proposed New Basel Capital Accord where such hedging operations are explicitly accounted as reducing the risk position of a bank. In this environment separation and full hedge results are derived.
urn:nbn:de:bvb:384-opus4-712340
Keywords: G21; G28; 330; credit risk; capital adequacy; regulation; risk aversion